2022
DOI: 10.3389/fneur.2022.915712
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Involvement in COVID-19 Among Non-Hospitalized Adolescents and Young Adults

Abstract: IntroductionCoronavirus disease 2019 (COVID-19) is prevalent among young people, and neurological involvement has been reported. We investigated neurological symptoms, cognitive test results, and biomarkers of brain injury, as well as associations between these variables in non-hospitalized adolescents and young adults with COVID-19.MethodsThis study reports baseline findings from an ongoing observational cohort study of COVID-19 cases and non-COVID controls aged 12–25 years (Clinical Trials ID: NCT04686734). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 56 publications
(65 reference statements)
1
23
2
Order By: Relevance
“…The lack of association of serum biomarkers of brain injury and infection status differs from previous studies, in which Ameres et al (Ameres et al 2020) found NfL to be elevated in adult health-care workers with a mild-to-moderate COVID infection and Havdal et al (Havdal et al 2022) found an increase in NfL and GFAP in non-hospitalized adolescents. This discrepant results to the latter study may be explained by the larger sample size, resulting in a more powered study and therefore, more likely to detect significant correlations.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The lack of association of serum biomarkers of brain injury and infection status differs from previous studies, in which Ameres et al (Ameres et al 2020) found NfL to be elevated in adult health-care workers with a mild-to-moderate COVID infection and Havdal et al (Havdal et al 2022) found an increase in NfL and GFAP in non-hospitalized adolescents. This discrepant results to the latter study may be explained by the larger sample size, resulting in a more powered study and therefore, more likely to detect significant correlations.…”
Section: Discussioncontrasting
confidence: 66%
“…This discrepant results to the latter study may be explained by the larger sample size, resulting in a more powered study and therefore, more likely to detect significant correlations. Moreover, our study investigated brain injury biomarkers in post-acute infection stages (60 days after infection), whereas Havdal et al (Havdal et al 2022) investigated biomarkers in the acute phase of the SARS-CoV-2 infection (not more than 28 days since the first day of symptoms or positive PCR test).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to show that women more often suffered from persistent fatigue, not caused by an effort and not alleviated by rest, within 12 weeks since the onset of the SARS‐CoV‐2 infection. So far, it has been known that among patients with mild COVID‐19, fatigue (Miyazato et al., 2022 ) and malaise after exertion were correlated with female sex (Havdal et al., 2022 ). In relation to the post‐COVID fatigue, these sex differences were also found significant in studies with similar to ours cross‐sectional design (Fugazzaro et al., 2022 ), and in cohorts consisting of medical workers of whom most did not require hospitalization due to COVID‐19 (Sultana et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown glial activation and neuronal injury in patients with COVID-19 [17,18] with elevated biomarkers related to neuronal injury detected in the cerebrospinal fluid (CSF) and blood of COVID-19 patients [19]. The concentrations of NfL and GFAP were found to be elevated in 405 non-hospitalized COVID-19 patients [20], with plasma GFAP levels observed to be significantly two-fold higher in critically ill patients with COVID-19 when compared to healthy controls [17]. Serum GFAP showed a significant association with the severity of COVID-19 infection [21], and both NfL and GFAP predicted COVID-19associated mortality in hospitalized patients [18].…”
Section: Introductionmentioning
confidence: 99%